1949
DOI: 10.1111/j.1365-2672.1949.tb03875.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitro‐compounds and Some Other Substances on Production of Hydrogen Sulphide by Sulphate‐reducing Bacteria in Sewage

Abstract: Summary. Development of hydrogen sulphidc in sewage, due to growth of sulphate‐reducing bacteria, is favoured by neutral or alkaline conditions and retarded by acidic conditions. Strains able to use lactate, formate, stearate, and cellulose as sources of carbon were detected by the use of appropriate media; no sulphate‐reducing bacteria capable of using tributyrin appeared to be present in the sample of sewage tested. Doses of chlorine much smaller than the chlorine demand delayed the formation of sulphide, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

1952
1952
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…The control of the growth and metabolic activities of Desulphovibrio desulphuricans is a problem of practical as well as of theoretical interest, in view of their role both in the anaerobic corrosion of ferrous pipes (von Wolzogen Kuhr & van der Vlugt, 1934; Bunker, 1936Bunker, ,1939 Hadley, 1943; Rogers, 1940Rogers, , 1945; Starkey &Wight, 1945; Starkey, 1947; Butlin &Vernon, 1949;Chemistry Research, 193846,1947 and in the pollution of water and sewage (Bunker, 1942; Rogers, 1945; Allen, 1949; Butlin, 1949). Hence the inhibition of these bacteria has been studied largely from a practical standpoint.…”
mentioning
confidence: 99%
“…The control of the growth and metabolic activities of Desulphovibrio desulphuricans is a problem of practical as well as of theoretical interest, in view of their role both in the anaerobic corrosion of ferrous pipes (von Wolzogen Kuhr & van der Vlugt, 1934; Bunker, 1936Bunker, ,1939 Hadley, 1943; Rogers, 1940Rogers, , 1945; Starkey &Wight, 1945; Starkey, 1947; Butlin &Vernon, 1949;Chemistry Research, 193846,1947 and in the pollution of water and sewage (Bunker, 1942; Rogers, 1945; Allen, 1949; Butlin, 1949). Hence the inhibition of these bacteria has been studied largely from a practical standpoint.…”
mentioning
confidence: 99%
“…Nitrates stimulate the activity of indigenous nitrate-reducing, sulfide-oxidizing bacteria (NR-SOB) to lower sulfide concentrations as well as stimulating heterotrophic denitrifiers that can outcompete SRB for energy sources (e.g., organic acids). The use of nitrate to control H 2 S odors in sewer and other wastewater streams has been known for many years and continues to be of commercial interest (1,5,8,16,22,47). More recently, Jenneman et al (32) and Jack et al (27) demonstrated that addition of nitrate to sulfide-laden oil field brines could also be used to remove sulfides in these waters.…”
mentioning
confidence: 99%
“…Naphthalene is also proved to be an effective controlling agent of SRB. As reported earlier the addition of high concentrations of nitrate can generate nitrous oxide, which increases the redox potential, leading to long-term inhibition of sulfide production (Allen, 1949;Jenneman, 1986). Naphthalene also proved to be toxic for the microorganisms using polycyclic aromatic hydrocarbons as carbon source (Gracia et al, 1998).…”
Section: Introductionmentioning
confidence: 76%
“…Therefore the need arises to make an extensive study on biological control of SRB. Nitrate is applied to control the growth of SRB and result in both transient and longterm inhibition of sulfide production (Allen, 1949). Naphthalene is also proved to be an effective controlling agent of SRB.…”
Section: Introductionmentioning
confidence: 99%